Methanolysis of Crude Jatropha Oil using Heterogeneous Catalyst from the Seashells and Eggshells as Green Biodiesel - A. N. R. REDDY; A. S. AHMED; M. D. ISLAM; S. HAMDAN (ASEAN Journal on Science and Technology for Development, 2015)
In this work, heterogeneous calcium oxide catalysts gleaned from Polymedosa expansa and eggshell were investigated for the transesterification of crude jatropha oil with methanol, to access their prospective performance in biodiesel production as an alternative green energy resource. The best yield of biodiesel achieved was 96% in 1 h for Step 1 using 0.01:1 ratio of acid catalyst to oil and 0.6:1 ratio of alcohol to oil ratio, together with 2 h of Step 2 using 0.02:1 ratio with base catalyst CaO, derived from P. expansa, to oil ratio and 5:1 ratio of alcohol to oil.  The properties of jatropha biodiesel were analyzed and found to have calorific value of 35.43 MJ/kg, density value of 895 kg/m3 and flash point of 167. The biodiesel was blended with mineral diesel from B0 to B50 for a diesel engine performance test. B20 indicated comparable characteristics with pure mineral diesel, like lowest fuel consumption rate, specific fuel consumption rate, highest brake horsepower and mechanical efficiency.